Body of lies - Johansen, Iris (Random House, Inc, 2002)
When a government official requests her unique skills of reconstruction to identify an unknown murder victim, forensic sculptor Eve Duncan is drawn into a deadly web of betrayal, intrigue, and murder as she tries to unlock the deadly secrets that someone will do anything to keep hidden.